Carbon Recycling Through CO2-Conversion for Stepping Toward a Cyclic-C Economy. A Perspective - Aresta, Michele; Dibenedetto, Angela (Frontiers in Energy Research, 2020)
The conversion of CO2 into added value chemicals, materials and fuels is a case of transition from the linear to the cyclic-C economy, a necessary change for stopping the putative negative effect of CO2 on climate and the environment. Several strategies can be implemented for CO2 conversion and their potential and timeframe is discussed in this perspective paper. The overall amount of avoided CO2 is evaluated in the short-, medium-, and long-term. The distinct contribution of Catalysis, Solar Chemistry and integrated Chemocatalysis-Biosystems is discussed.